The Analysis of KPU Karawang Strategy in Building Political Culture through Voter Education - Ardian, Muhtar Galuh (Nexus Publishing NXP, 2024)
General elections provide the Election Commission (KPU) with an opportunity to educate the public on actively participating in the political process. Public political participation in general elections is not only about exercising their voting rights or mobilizing masses for the interests of election participants, but also about expressing their political awareness in determining the direction of government policies through the vision, mission, and programs of election participants. Public political awareness can be cultivated through voter education organized by the KPU. As a result, voter education has a positive implication in building a participatory political culture among the public and managing political polarization by equipping people with the knowledge to become rational voters. Rational voters indirectly influence societal consensus and social cohesion towards the government.